Poetry for EFL classroom: Students’ self-expression and the creative process behind its creation - Mardiningrum, Arifah; Adriyanthi, Nisrina (Universitas Islam Negeri Palangka Raya, Indonesia, 2023)
In learning and teaching English as a foreign language, poetry has been used in several non-literary classes but in relatively small proportions, and the foci were mainly not on the students' self-expression and individual creative process. This research aims to understand the experiences of student-teachers majoring in English in using poetry as a means of self-expression and their creative process. This study was conducted with a qualitative approach involving six student-teachers enrolled in the English Language Study Program of a Southern Yogyakarta University, Indonesia. Data were collected through in-depth interviews and analyzed through coding. The results show that poetry became a place for self-reflection, sharing personal experiences, a place for self-awareness, and freedom of expression. Meanwhile, the creative process that the students experienced consists of receiving examples, reliving memories, free writing, finding the right place and atmosphere, writing and re-writing, and receiving and responding to feedback. The study implied that poetry could benefit students with a planned and lengthy process. The study might contribute to the field of language education by providing insights into how poetry can be incorporated into the teaching and learning process.